Architectural archives developing an appraisal, preservation, reference and access program for selected agencies in Metro Manila - Cansancio, Emmielouisa A.; Punzalan, Ricardo L.; Montesa, Teresa S.; Granda, Yolanda C. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Architectural archives are us, as a people and as a nation. These are indicative of the society's past, the simultaneous awareness and orientation of the present, and the directive guidance for the future. However, little does a society understand and appreciate that architectural archives exude more than an eloquent testimony of history than what a three-dimensional structure discloses. Ideally, the built and written evidences ought to exist together to completely document the built heritage. But societal priorities and considerations vary greatly, thereby causing turmoil to values placed over the built heritage. The architectural archives seriously suffer from neglect and in the inadequacies on their appraisal, preservation and access. Consequently, the society has taken a less active role in keeping architectural emblems - the same hold true with the architectural archives.
The study probed into the appraisal, preservation, reference and access principles applied to architectural archives in selected agencies to provide baseline data needed for the development of a sound appraisal, preservation, reference and access program. Under the umbrella of descriptive research, survey research was employed in the pursuance of the objectives in this study. Data gathered were comparatively analyzed with the standard archives practices for architectural archives. Findings revealed that there is a serious lack of knowledge on the preservation and care for architectural archives.
Thus, current practices on the appraisal, preservation, reference and access do not conform to the standard archives practices. Moreover, the allocation of funds for an architectural archives program was considered as the most formidable element that retrains the respondents from establishing an archives program. With these problems at hand, the study recommends an appraisal, preservation, reference and access program for the architectural archives to curb and halt unaccepted archives practices, thereby, advancing the archives continuing value of the built heritage.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Architecture -- Philippines -- Manila Metropolitan Area -- Archival resources